Autophagy Functions to Prevent Methylglyoxal-Induced Apoptosis in HK-2 Cells. (4th June 2020) - Park, So-Hyun; Choi, Hyun-Il; Ahn, Jiyun; Jang, Young-Jin; Ha, Tae-Youl; Seo, Hyo-Deok; Kim, Yoon-Sook; Lee, Dae-Hee; Jung, Chang Hwa
Abstract : Methylglyoxal (MGO), a reactive carbonyl species, causes cellular damage and is closely related to kidney disease, particularly diabetic nephropathy. Although MGO has been reported to induce autophagy and apoptosis, the relationships between the two pathways are unclear. Here, we evaluated whether autophagy may be the underlying mechanism inhibiting MGO-induced apoptosis. MGO treatment induced concentration- and time-dependent apoptosis in HK-2 cells. Moreover, MGO upregulated the autophagy markers p62 and LC3-II. Apoptosis caused by MGO was increased in ATG5-knockdown cells compared to that in wild-type cells. In contrast, autophagy activation by 5-aminoimidazole-4-carboxamide ribonucleotide resulted in reduced apoptosis, suggesting that autophagy played a role in protecting against MGO-induced cell death. To examine the mechanisms through which autophagy occurred following MGO stimulation, we investigated changes in AKT/mammalian target of rapamycin (mTOR) signaling. Autophagy induction by MGO treatment was not related to AKT/mTOR signaling; however, it did involve autophagy-related gene expression promoted by AMP-activated protein kinase-mediated transcription factors, such as forkhead box 1. Overall, our findings indicate that MGO-induced cellular damage can be mitigated by autophagy, suggesting that autophagy may be a potential therapeutic target for diseases such as diabetic nephropathy.